The Mechanism of Organizational Citizenship Behavior for the Environment in Improving Environmental Performance Across Different Industrial Sectors: A Systematic Review - Miftah Faiz Ali Ramdhani; Siti Nurjanah; Despinur Dara; Mahmud Ali (Journal of Business and Behavioural Entrepreneurship, 2026)
Green Organizational Citizenship Behavior (GOCB) is a key construct in supporting environmental performance across various industrial sectors. This study employs a systematic literature review (SLR) based on the PRISMA framework, analyzing 45 articles (2016–2026) to understand the mechanisms linking Green Human Resource Management (GHRM) practices, green leadership, employee motivation, and environmental outcomes. Results indicate that GOCB is influenced by individual capacity, social interactions, HR practices, and transformational green leadership. Training, rewards, and organizational culture play a crucial role in fostering voluntary pro-environmental behavior. Cross-cultural analysis highlights variations in the effectiveness of GOCB mechanisms according to geographical and regulatory contexts. This study also emphasizes the dominance of quantitative methods and the need for qualitative or mixed-methods approaches to understand the dynamics of pro-environmental behavior more deeply. Key contributions include a synthesis of GOCB mechanisms, cross-theoretical integration (AMO, SET, Social Learning Theory, COR), and the identification of research gaps in developed and cross-cultural contexts. Future research is recommended to use mixed-method designs, expand the scope of industries and regions, and incorporate cultural and institutional variables to strengthen theoretical models and practical applications.